Implementation of an Interactive Reading Corner to Enhance Elementary School Students' Reading Literacy - Sari, Fransiska Faberta Kencana (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study intends to analyze the implementation of the Interactive Reading Angle as?a strategy to improve reading literacy in elementary school. With reading books and digital technology, the Interactive Reading Corner can also?be accessibile by visual media. This qualitative study has?a case study design. Data collection methods consisted of observation, interviews, and documentation in classrooms where the Interactive Reading Corner had been?applied. It was found that Interactive Reading Corner helps to enhance students' interest in reading through a variety of reading materials displays, the vocabulary growth will be increased by providing diverse reading materials and this is aligned with a variety of types and types of text exposures, enhancing students' understanding of reading materials through displaying visual elements and discussion between students or teachers?accompanying reading activities. Moreover, engagement in the Reading Corner encourages students to?read independently more often. Study finding Interactive Reading Corner can serve as an effective new reading platform for improving students’ reading literacy. The study concludes that the Interactive Reading?Corner has a positive impact on improving students’ reading literacy. The limitation of this study was that it was conducted?at only one school, thus unfortunately preventing the results from being widely generalizable, as of yet. It suggests introducing a reading corner in more?schools for an extended period to get a clearer idea.